(untitled) (Fiep Bulletin - online, 2015)
The subject constitutes a rare occasion for discussion because of the complexity of its problems, above all because enlightened and reliable specialists are called to think on it. They did not come to this Congress to deal with matters already easily solved, but to examine together controversial points of view, the explanation of which is considered fundamental for the adequate planning of their future professional activity.